Polyphenol co-pigments enhanced the antioxidant capacity and color stability of blue honeysuckle juice during storage - Yifan Geng; Kaojia Cui; Na Ding; Houping Liu; Junwei Huo; Xiaonan Sui; Yan Zhang (Food Chemistry: X)
The study aimed to assess the impact of incorporating five co-pigments (gallic acid, quercetin, rutin, catechin, and epigallocatechin gallate (EGCG)) on the color stability of blue honeysuckle juice (BHJ). Additionally, it sought to determine the influence of varying proportions of anthocyanins in an accelerated test (light at 40 °C for 24 d). Results indicated that the addition of polyphenol co-pigments effectively mitigated the thermal degradation of anthocyanins, enhancing color saturation and antioxidant capacity of BHJ. Notably, quercetin, rutin, catechin, and EGCG exhibited superior efficacy compared to gallic acid. FTIR analysis revealed non-covalent complex formation between co-pigments and anthocyanins, including hydrogen bonds and van der Waals forces, thereby shielding them from degradation. HPLC-ESI-QTOF-MS2 identified 15 anthocyanins and 39 non-anthocyanin polyphenols. Addition of co-pigments effectively curbed anthocyanin degradation, thus stabilizing juice system. Consequently, judicious incorporation of co-pigments holds promise as a technology for enhancing the color quality and stability of BHJ during processing.